PROCEDURAL KNOWLEDGE-BASED STRATEGIES IN IMPROVING STUDENT LEARNING OUTCOMES IN ORDINARY DIFFERENTIAL EQUATIONS COURSES - Lapele, Dina Amalya; Jait, Adam Bin Haji (MATEMATIKA DAN PEMBELAJARAN, 2023)
This research aims to identify the differences in average learning outcomes between students taught using procedural knowledge-based strategies and students who are taught without using procedural knowledge-based strategies. This research is quasi experimental research with a posttest-only design with nonequivalent groups. The population in this study were students from the Mathematics Education Department at IAIN Ambon. The samples used were students of the IAIN Ambon Mathematics Education Department Semester 3 (class A and class B). The number of class A students is 14 people and the number of class B students is also 14 people. The data collection technique in this research was tests. The instrument used is in the form of test questions. The test questions consist of three questions describing various types of ordinary differential equations. The data analysis technique used were the Mann Whitney U Test and descriptive test. The research results showed that there were differences in average learning outcomes between students who were taught using procedural knowledge-based strategies (experimental class) and students who were taught without using procedural knowledge-based strategies (control class). The average learning outcomes of experimental class students is higher than the average learning outcomes of control class students.